Molecular Design of Hole Transport Materials to Immobilize Ion Motion for Photostable Perovskite Solar Cells - Zhang, Zheng; Duan, Chenghao; Wang, Sijing; Xie, Tianyou; Zou, Feilin; Luo, Yang; Tang, Ruijia; Guo, Kunpeng; Yuan, Ligang; Zhang, Kaicheng; Wang, Yao; Qiu, Jianhang; et al. (Angewandte Chemie International Edition, 2024)
Poor operational stability is a crucial factor limiting the further application of perovskite solar cells (PSCs). Organic semiconductor layers can be a powerful means for reinforcing interfaces and inhibiting ion migration. Herein, two hole-transporting molecules, pDPA-SFX and mDPA-SFX, are synthesized with tuned substituent connection sites. The meta-substituted mDPA-SFX results in a larger dipole moment, more ordered packing, and better charge mobility than pDPA-SFX, accompanying with strong interface bonding on perovskite surfaces and suppressed ion motion as well. Importantly, mDPA-SFX-based PSCs exhibit an efficiency that has significantly increased from 22.5 % to 24.8 % and a module-based efficiency of 19.26 % with an active area of 12.95 cm2. The corresponding cell retain 94.8 % of its initial efficiency at maximum power point tracking (MPPT) after 1,000 h (T95=1,000 h). The MPPT T80 lifetime is as long as 2,238 h. This work illustrates that a small degree of structural variation in organic compounds leaves considerable room for developing new HTMs for light stable PSCs.
CRIS-Team Scopus Importer:2024-10-25
Keywords: hole-transporting molecule; interface bonding; ion migration; perovskite solar cells; photostability